Quantification of within-patient Staphylococcus aureus phenotypic heterogeneity as a proxy for the presence of persisters across clinical presentations. (July 2022) - Bär, Julian; Boumasmoud, Mathilde; Mairpady Shambat, Srikanth; Vulin, Clément; Huemer, Markus; Schweizer, Tiziano A.; Gómez-Mejia, Alejandro; Eberhard, Nadia; Achermann, Yvonne; Zingg, Patrick O.; Mestres, Carlos A.; Brugger, Silvio D.; et al.
Abstract: Objectives: Difficult-to-treat infections caused by antibiotic-susceptible strains have been linked to the occurrence of persisters, a subpopulation of dormant bacteria that tolerate antibiotic exposure despite lacking genetic resistance. These persisters can be identified phenotypically by plating on nutrient agar because of their altered growth dynamics, resulting in colony-size heterogeneity. The occurrence of within-patient bacterial phenotypic heterogeneity in various infections and clinical determinants of persister formation remains unknown. Methods: We plated bacteria derived from 132 patient samples of difficult-to-treat infections directly on nutrient-rich agar and monitored colony growth by time-lapse imaging. We retained 36 Staphylococcus aureus monocultures for further analysis. We investigated clinical factors associated with increased colony growth-delay with regression analyses. We corroborated the clinical findings using in vitro grown static biofilms exposed to distinct antibiotics. Results: The extent of phenotypic heterogeneity of patient-derived S. aureus varied substantially between patients (from no delay to a maximum of 57.6 hours). Increased heterogeneity coincided with increased median colony growth-delay. Multivariable regression showed that rifampicin treatment was significantly associated with increased median growth-delay (13.3 hours; 95% CI 7.13–19.6 hours; p < 0.001). S. aureus grown in biofilms and exposed to high concentrations of rifampicin or a combination of rifampicin with clindamycin or levofloxacin exhibited prolonged growth-delay (p < 0.05 for 11 of 12 comparisons), correlating with a strain-dependent increase in antibiotic tolerance. Discussion: Colony-size heterogeneity upon direct sampling of difficult-to-treat S. aureus infections was frequently observed. Hence, future studies are needed to assess the potential benefit of phenotypic heterogeneity quantification for staphylococcal infection prognosis and treatment guidelines. Graphical abstract: Image 1